Viscous Flow Approach to “Pushing Out Old Water” from Undisturbed and Repacked Soil Columns - Bogner, C. (2020)
The application of bromide tracer in transient infiltration–drainage experiments on undisturbed and repacked soil columns revealed distinct delays of tracer front arrivals with respect to the wetting front arrivals. A viscous flow approach was matched to the flow data that resulted in the parameters film thickness F and specific contact area L of the mobile water with the stagnant parts of the porous medium. Various combinations of F and L were related to the tracer delays, where the combinations L × F, L × F 3, and L × F 2 increasingly showed the highest correlation. The volume of mobile water was turned over 3.8 to 29.5 times between the arrivals of the wetting fronts and the arrivals of the tracer fronts. The delays and their statistical interpretations in view of the viscous flow approach are considered a significant contribution to the understanding of the phenomenon of “pushing out old water” that is still obscured in the hydrology of hillslopes and catchments. Despite the lack of a satisfying explanation for the high numbers of mobile‐water turnovers, the fact that the phenomenon of “pushing out old water” already occurs in soil columns may stimulate its investigation at the soil profile scale.